Location of trauma care resources with inter-facility patient transfers. (2021) - DuBois, Eric; Schmidt, Adam; Albert, Laura A.
Abstract: Traumatic injury is the third leading cause of death in the United States and is the leading cause of death among people aged 1–44. Regional trauma care systems can significantly reduce this mortality rate if resources are located and used appropriately. Trauma centers are categorized as able to either provide total care (Level I or II) or prompt care (Level III and IV). We study trauma system planning by introducing an integer programming model to optimally relocate existing air ambulances, locate new air ambulances, and upgrade Level III and IV trauma centers to Level I or II trauma centers within a mature trauma system. The goal of these models to improve timely access to care and ensure the appropriate level of care is provided to severely injured patients. A novel aspect of the modeling approach is the inclusion of patient transfers from Level III/IV trauma centers to Level I/II trauma centers. Patient transfers are of particular importance after mass casualty events when a surge of trauma patients can overwhelm local trauma center capacity. As a result, we introduce a mass casualty incident response stochastic programming model to optimally relocate air ambulances within the trauma system following a mass casualty incident but before patient demand is known with certainty. The two models inform planning decisions by considering the interrelated response decisions. We construct case studies for both models based on the Wisconsin, USA trauma care system. The results highlight the importance of relocating air ambulances for increasing the number of patients transported directly to a Level I/II trauma center. The results also indicate that considering patient transfers within the model can significantly alter the optimal locations of trauma care resources compared to when transfers are not considered. Highlights: Patient transfers from low-level trauma centers to high-level centers save lives. We model trauma system planning that includes patient transfers and air ambulances. We also consider incidence response decisions after mass casualty events. We present optimization models to address planning with patient transfers. Case studies demonstrate the value of patient transfers by air ambulances.